The Effect Of Organizational Culture On Organizational Commitment In Syrian Public Universities- A Field Study In Tishreen University - كندة علي ديب; لينا فياض; عفراء عدنان عجين (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aimed to investigate the effect of organizational culture on organizational commitment in Tishreen University, The researcher collected the data through a questionnaire is prepared based on previous studies, and the class random sampling was applied during the distribution of the questionnaire to the research community, which includes academics and administrative staff, and data were analyzed by using statistical analyzing program SPSS20. The field study conducted by the researcher found there is a very weak significant effect of dominant organizational culture on organizational commitment, as it was found that there is a weak significant effect of dominant organizational culture on continuous commitment. In addition, there is a very strong significant effect of dominant organizational culture on normative commitment; the results also showed there is a weak significant effect of dominant organizational culture on organizational commitment in Tishreen University. The researcher recommended stressing the importance of organizational commitment at Tishreen University, by using appropriate means such as periodic evaluation of performance and the development of an effective reward system, as well as university should focus on organizational culture by creation its own rituals such as group ceremonies and material or moral honor to individual and collective achievers.